Effect of Standardized Warfarin Treatment Protocol on Anticoagulant Effect: Comparison of a Warfarin Medication Therapy Adherence Clinic with Usual Medical Care - Salihah Aidit; Yee Chang Soh; Chuan Seng Yap; Tahir M. Khan; Chin Fen Neoh; Chin Fen Neoh; Shazwani Shaharuddin; Yaman W. Kassab; Rahul P. Patel; Long C. Ming; Long C. Ming (Frontiers in Pharmacology, 2017)
Objective: To evaluate the impact of pharmacist-led warfarin management and standardized treatment protocol.Methods: A retrospective cohort study was carried out in a cardiology referral hospital located in central Kuala Lumpur, Malaysia, from 2009 to 2014. The inclusion criteria were: adult patients who were diagnosed and treated for atrial fibrillation (AF) with warfarin, attended the warfarin medication therapy adherence clinic (WMTAC) for at least 12 weeks, and with at least four international normalized ratio (INR) readings. The electronic medical records were reviewed for demographics, type of AF, warfarin dose, INRs, adverse events, co-morbidities, and drug–drug interactions. The outcome measures included the mean time to therapeutic INR, the mean percentage of time in therapeutic range (TTR), bleeding events, and common drug interactions.Results: Out of 473 patients, 151 patients fulfilled the inclusion criteria. The findings revealed that there were significant associations between the usual medical care (UMC) group and pharmacist-led WMTAC in terms of TTR (p = 0.01) and INR (p = 0.02) levels. A positive impact of pharmacists’ involvement in the WMTAC clinic was where the “pharmacist’s recommendation accepted” (p = 0.01) and “expanded therapeutic INR range” (p = 0.04) were statistically significantly higher in the WMTAC group.Conclusion: There was a significant positive association between the pharmacist-led WMTAC and anticoagulation effect (therapeutic TTR, INR). The identified findings revealed that expanded role of pharmacist in pharmacist-managed warfarin therapy is beneficial to optimize the warfarin therapy. This study also highlighted the critical roles that pharmacists can actively play to ensure optimal anticoagulation pharmaceutical care.Key messages:What is already known on this subject?• Pharmacist-managed warfarin therapy is beneficial for optimizing warfarin therapy. In such therapy, recommendations such as dose adjustment and safer alternative drugs (given drug–drug interactions and/or food–drug interactions) are made.• The active involvement of pharmacists in warfarin adherence clinics could significantly improve adherence.• However, the warfarin treatment outcomes from UMC, pharmacist-and-physician-led care and pharmacist-led care have not been studied.• The impact of the implementation of the standardized protocol for the warfarin adherence clinic has not been assessed.What this study adds?• INR levels among UMC group and WMTAC group were significantly different.• Though the TTR level for the WMTAC group was not significantly different than the UMC group, it was higher and close to the targeted 60% level.• The identified findings show that pharmacists’ focus on intervention for missed doses, adherence and dose adjustment provide positive impact on patients’ warfarin therapy.